Conceptualization of Gratitude : Qualitative and Quantitative Approach - Rini Risnawita Suminta; Akhmad Hasan Saleh (Program Studi Psikologi Islam (IAIN) Kediri, 2021)
Research on the development of the concept of gratitude with Indonesian participants is quite important, considering that in Indonesia until now there has been no instrument specifically used to measure or assess the concept of gratitude that was developed based on Indonesian citizens. The purpose of this study is to develop the concept of a thanksgiving scale using qualitative and quantitative approaches. The study participants were 129 students of IAIN Kediri. The scale used in this study is based on the results of the first study conducted qualitatively. The second research analysis using exploratory factor analysis and confirmatory factor analysis. The results of an exploratory analysis conducted on data from all research subjects, obtained the results that the gratitude of the subject is organized into three factors, namely the factor of recognizing favors, receiving favors and praising Allah for favors. Based on the confirmatory analysis it was found that chi-square 135,570 (DF = 88, p = 0.001), CMIN / DF = 1.541, GFI = 0.884, AGFI = 0.841, TLI = 0.904 and RMSEA = 0.065. Thus the criteria for acceptance of the model can be met or are in accordance with the requirements. Thus it can be stated that the proposed model design is the same as empirical data or the proposed model is fit.